DAYA ANTIFUNGI REBUSAN KULIT BATANG JAMBU METE (Anacardium occidentale L.) TERHADAP C. albicans PADA RESIN AKRILIK - Ria Lidyawita; Sudarsono Sudarsono; Harsini Harsini (Majalah Obat Tradisional, 2013)
Lack of dental care will be resulted in the increased colonies of C. albicans if the dental care was not in ordinary condition that can cause denture stomatitis. C. albicans is common in denture wearer and is found as many as 86% of patients with denture stomatitis. Cashew bark contains tannins, gallic acid and anacardic acid, phenolic compounds which are responsible for the antifungal activity against C. albicans. This research consisted of determination of total phenolic compound by Folin Ciocalteu method, and the antifungal test against C. albicans in acrylic resin plate. Acrylic resin plate was immersed in a suspension of C. albicans for 24 hours, rinsed with Phospate Buffered Saline (PBS), soaked with agitation for 3 minutes in a solution of cashew stem bark 12.5%w/v, 25%w/v, and 50% b/v with 20 mg/ml stock, vibrated in physiological saline, incubated on Sabouraud order for 48 hours. At the end of the experiment, the inhibition of C. albicans growth was observed and calculated. Anava and Kruskal-Wallis test were used to determine the significance difference between groups. Water extract of stem bark in the concentration of 12,5%w/v, 25%w/v, and 50% w/v had phenolic total value of 35,18% w/w EAG, 31,64%w/w EAG, 29,47%w/w EAG. It could inhibit C. albicans by 69.69%, 82.66%, 94.14% respectively.